Dealing with urban poverty: the case of Ezbet Bekhit, Manshiet Nasser - Abdel Azim, Nazly Amr (AUC Knowledge Fountain, 2011)
The objective of this research is to examine the effectiveness or lack thereof of community-based organizations (CBOs) in alleviating poverty in Ezbet Bekhit, Manshiet Nasser, with a special focus on employment creation. This is achieved by studying the organizational structure of these CBOs; their links with larger organizations and their role in wider development plans; their definitions of poverty and their visions and strategies for poverty alleviation in addition to initiatives targeting employment creation; the sustainability of these CBOs and their initiatives, and finally the employment prospects for the inhabitants of Ezbet Bekhit.